Strategy for Development of Micro Waqf Banks in Improving Community Welfare in West Sumatra (Case Study of LKSM BWM PPM Al-Kautsar District of Fifty Cities) - Nurhafiani Nurhafiani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the strategy for development of micro waqf banks in improving community welfare in west Sumatra (case study of LKSM BWM PPM Al-Kautsar District of Fifty Cities). The data analysis technique used is the SWOT (Strength, Weakness, Opportunity, Threats) analysis method. The strategy for developing PPM Al-Kautsar Micro Waqf Banks is based on the results of the SWOT matrix analysis, which shows that the strategy that can be carried out in developing Micro Waqf Banks is the SO Strategy by using all strengths to take advantage of existing opportunities. Low consistency of mentoring services (selling), without collateral and interest by utilizing the government restructuring program, utilizing the role of the kyai in establishing good cooperation and building trust with institutions, local governments, the community socializing the existence of BWM, conducting Halmi routines virtually during a pandemic in providing education, direction, education to customers, improving the quality of services and products even though there is already a pick-up system, optimizing the empowerment of assistance through digital so that customers can survive during the pandemic despite social restrictions but empowerment continues. As a strategy that can be done to develop BWM itself, namely utilizing BWM digitization in providing virtual education, promoting customer products through e-commerce and social media, Utilizing the role of clerics in disseminating the BWM program to the public. The impact of the existence of the PPM Al-Kautsar Micro Waqf Bank on the Welfare of the Community in the Fifty Cities District is proven by measuring the customer's ability after financing at the Al-Kautsar PPM BWM. The increase in welfare can be measured by welfare indicators in the form of fulfilling basic needs (Darurriyat) in maqasid sharia.